UNRAVELING THE SEQUENCE AND STRUCTURE OF THE PROTEIN OSTEOCALCIN FROM A 42 KA FOSSIL HORSE - Ostrom P.H.; Gandhi H.; Strahler J.R.; Walker A.K.; Andrews P.C.; Leykam J.; Stafford T.W.; Kelly R.L.; Walker D.N.; Buckley M.; Humpula J. (My University, 2006)
We report the first complete amino acid sequence and evidence of secondary structure for osteocalcin from a temperate fossil. The osteocalcin derives from a 42 ka equid bone excavated from Juniper Cave, Wyoming. Results were determined by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-MS) and Edman sequencing with independent confirmation of the sequence in two laboratories. The ancient sequence was compared to that of three modern taxa: horse (Equus caballus), zebra (Equus grevyi), and donkey (Equus asinus). Although there was no difference in sequence among modern taxa, MALDI-MS and Edman sequencing show that residues 48 and 49 of our modern horse are Thr, Ala rather than Pro, Val as previously reported (Carstanjen B., Wattiez, R., Armory, H., Lepage, O.M., Remy, B., 2002. Isolation and characterization of equine osteocalcin. Ann. Med. Vet. 146(1), 31-38). MALDI-MS and Edman sequencing data indicate that the osteocalcin sequence of the 42 ka fossil is similar to that of modern horse. Previously inaccessible structural attributes for ancient osteocalcin were observed. Glu39 rather than Gln39 is consistent with deamidation, a process known to occur during fossilization and aging. Two post-translational modifications were documented: Hyp9 and a disulfide bridge. The latter suggests at least partial retention of secondary structure. As has been done for ancient DNA research, we recommend standards for preparation and criteria for authenticating results of ancient protein sequencing. © 2006 Elsevier Inc. All rights reserved.